EPIGENOMICS OF MAIZE HYBRIDS WITH REFERENCE TO KERNEL WEIGHT - & et al., Elsahookie (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Hybrid vigour is one of the most important phenomena became in practice all over the world for its higher performance in maize and several other genera of crops, vegetables, and fruit crops. There is no single theory explains this phenomenon. The only general rule known about having hybrid vigour is that crossing between two genetically diversed inbreds. Epigenomics is thought to be involved in hybrid vigour. However, exact timing of maternal and paternal genomes after fertilization of the endosperm is still not totally understood. It is still believed that the ratio of maternal to paternal gene expression through endosperm development is 2m:1p. The diverged methylation level of the crossed inbreds could be involved in hybrids of maize, at least in part.